Analisis Kinerja Keuangan Sektor Manufacture dengan Multiple Discriminant Analysis Bankcruptcy Model di Bursa Efek Indonesia Periode 2014 – 2017 - Yunan Surono; Sindy Dwiroro Pangestu (Universitas Batanghari, 2019)
This research aims to prove the financial performance of Manufacture sector with Multiple Discriminant Analysis Bankruptcy Model when measured using the Altman's Z-score first model, Altman's Z-score revision and Altman's Z-score modifications, Springate model and Zmiejewski model as well as to get the stocks that have the best performance based on the model. In this research the population used is the stock sector manufacturing group on the Indonesia Stock Exchange in the year 2014 – 2017 as many as 166 issuers manufacture. This research sample is the manufacture sector company, which provides complete data, and has a total asset of positive value and fluctuates as many as 22 companies. This form of research is an explolanatoris research (explanatory Research). The results showed, that based on the first Altman's Z-score model, in 2014 the company's performance in a healthy or not bankrupt category was 31.82%, while the company had a gray performance of 22.73%, as for The company's performance with the category broke by 45.45%. In 2015 the company's performance with a healthy category of 27, 27, 82%, a company that had a gray performance of 27.27%, the company's performance of the category went bankrupt by 45.45%. In 2016 the company's performance with a healthy category of 22, 73, 82%, the company had a gray performance of 36.36%, as for the performance of the company with the category bankrupt by 36.36%. In 2017 the company's performance with a category of 40.91%, the company has a gray performance of 22.73%, as for the performance of the company with the category bankrupt by 36.36%. Based on the model Altman Z-Score revision can be concluded that in 2014 the company's performance with a healthy category of 31.82%, a company that has a gray performance of 54.55%, as for the performance of the company with the category bankrupt 13.64%. Year 2015 the performance of the company with a healthy category of 27.27%, the company has a gray performance of 54.55%, the company with the category went bankrupt by 18.18%. Year 2016 the company's performance with a healthy category of 45.45%, while the company has a gray performance of 36.36%, the company with the category went bankrupt by 18.18%. Year 2017 the performance of the company with a healthy category of 50.00%, the company that has a gray performance of 31.82%, the performance of the company with the category bankrupt by 18.18%. Based on the model of Altman Z-score modification can be concluded, namely in 2014 the performance of the company with a healthy category of 72.73%, the company that has a gray performance of 22.73%, as for the performance of the company with the category bankrupt of 4.55%. In 2015 the company's performance with a healthy category of 72.73%, while the company had a gray performance of 18.18%, as for the company's performance in the category went bankrupt by 9.09%. In 2016 the company's performance with a healthy category of 77.27%, the company had a gray performance of 13.64%, the company's performance in the category went bankrupt by 18.18%. In 2017 the company's performance with a healthy category of 81.82%, while the company had a gray performance of 13.64%, as for the company's performance in the category went bankrupt by 4.55%. Based on Springate model can be concluded, namely in 2014 the performance of the company with a healthy category of 59.09%, while companies that have a gray performance is not there, as for the performance of the company with the category bankrupt by 40.91%. In 2015 the company's performance with a healthy category of 50.00%, while companies that had a gray performance did not exist, the performance of the company with the category went bankrupt by 50.00%. In 2016 the company's performance with a healthy category of 59.09%, while companies that have a gray performance does not exist, as for the performance of the company with the category bankrupt by 40.91%. In 2017 the company's performance with a healthy category of 63.64%, while companies that have a gray performance does not exist, as for the performance of the company with the category bankrupt by 36.36%. Based on Zmiejewski model can be concluded, in 2014 to 2017 the performance of companies with a healthy or not bankrupt category is 100%, while companies that have a gray performance does not exist, as for the performance of the company with Bankruptcy category does not exist. Stocks that have the best performance based on each multiple discriminant analysis bankruptcy models respectively, namely INTP, CEKA, MERK, GGRM, LMSH, CPIN, MLBI, IKBI, TRIS UNIC and INDF, who have never experienced bankruptcy or in financial distress.